2014
DOI: 10.1136/jmedgenet-2014-102798
|View full text |Cite
|
Sign up to set email alerts
|

Whole exome sequencing in family trios revealsde novomutations inPURAas a cause of severe neurodevelopmental delay and learning disability

Abstract: BackgroundDe novo mutations are emerging as an important cause of neurocognitive impairment, and whole exome sequencing of case-parent trios is a powerful way of detecting them. Here, we report the findings in four such trios.MethodsThe Deciphering Developmental Disorders study is using whole exome sequencing in family trios to investigate children with severe, sporadic, undiagnosed developmental delay. Three of our patients were ascertained from the first 1133 children to have been investigated through this l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
120
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(135 citation statements)
references
References 39 publications
14
120
1
Order By: Relevance
“…In previous studies, the transition of dendritic protein MAP2 is thought to be Purα-dependent, Hokkanen's work also found the changes of this protein's expression and distribution. Same as Khalili's work, they also found that the PURA knock-out mice developed a continuous tremor at the age of 2 weeks and this symptom continued throughout lifetime; this observation is consistent with Khalili's report, it indicates that disruption the endogenous level of Purα expression would be associated with the onset of epilepsy, this phenomenon is also confirmed by other researches related to the changes of Purα [19,29], about this we will discuss later in the review.…”
Section: Postnatal Brain Development Was Affected When Purα Has Been supporting
confidence: 76%
See 1 more Smart Citation
“…In previous studies, the transition of dendritic protein MAP2 is thought to be Purα-dependent, Hokkanen's work also found the changes of this protein's expression and distribution. Same as Khalili's work, they also found that the PURA knock-out mice developed a continuous tremor at the age of 2 weeks and this symptom continued throughout lifetime; this observation is consistent with Khalili's report, it indicates that disruption the endogenous level of Purα expression would be associated with the onset of epilepsy, this phenomenon is also confirmed by other researches related to the changes of Purα [19,29], about this we will discuss later in the review.…”
Section: Postnatal Brain Development Was Affected When Purα Has Been supporting
confidence: 76%
“…Another recently discovered neurodegenerative disorder is Fragile X-associated tremor/ataxia syndrome [15], the adult carriers of permutation alleles (55-200 CGG repeats) of the fragile X mental retardation 1 [16] gene [17,18] would be affected. In addition, another neuronal developmental disorder linked with Purα is 5q31.3 Microdeletion Syndrome reported by Lalani et al [19] and Hunt et al [20]. For more detailed information about Purα please refer to the review written by Johnson EM [5,21], White MK [22] and Chai J et al [40].…”
Section: Introductionmentioning
confidence: 99%
“…Three genes in our epilepsy cohort (COQ4, DNM1, and PURA), accounting for 14% (3/21) of all novel genetic etiologies identified in patients with epilepsy, were subsequently confirmed in independent publications. 16,[33][34][35][36] Although it is difficult to assess to what extent this frequency is higher than would be expected by chance, we feel reassured by the fact that approximately 15% of all genes that were reported as potential novel disease genes received subsequent independent confirmation without knowledge of our prior report. This number may provide a baseline for future studies examining the role of diagnostic novel gene reporting.…”
Section: Validation Of Novel Genetic Etiologiesmentioning
confidence: 80%
“…Of the 119 positive/likely positive cases, 105 (88.2%) patients were found to have pathogenic/likely pathogenic mutations in previously characterized disease genes ( 35,36 after the clinical DES report was issued. The authors of these publications were unaware of our reports, and our patients were not included in the respective publications.…”
Section: Characterization Of Molecular Findingsmentioning
confidence: 99%
“…Another recently discovered neurodegenerative disorder is fragile X-associated tremor/ataxia syndrome [15], the adult carriers of premutation alleles (55 to 200 CGG repeats) of the fragile X mental retardation 1 [16] gene [17,18] would be affected. In addition, another neuronal developmental disorder linked with Purα is 5q31.3 Microdeletion Syndrome reported by Lalani et al [19] and Hunt et al [20]. For more detailed information about Purα please refer to the review written by Johnson [5,21], White [22] and Chai et al [23].…”
Section: Introductionmentioning
confidence: 99%